The influence of red and blue font color on intertemporal choice: the mediating roles of time perception and dimensional difference comparison - Kai Zhang; Hui Jiang; Xiaowei Geng (BMC Psychology)
Abstract Background Intertemporal choices are the process by which people make choices about losses or gains at different points in time (near or far). To explore the relationship between font color and intertemporal choice and to examine the serial mediation of time perception and intradimensional difference comparison on the association between font color and intertemporal choice on the basis of attribute-based choice models. Methods We randomly assigned subjects to the intertemporal choices questionnaire in a specific font color (blue vs. red) condition. The Intertemporal Choice Task, the Subjective Duration Judgment Task and the Intradimensional Difference Comparison Task were administered to a sample comprising 210 college students (103 males accounting for 49.05%). Multivariate analysis and latent variable analysis were used to explore the separate mediating roles of time perception and intradimensional difference comparison in the association between font color and intertemporal choice, and their serial mediation was also investigated. The bootstrap method was employed to test the significance of these mediating effects. Results Compared with red font, blue font can encourage students to choose more-farsighted intertemporal choices (i.e., LL). Students who use the blue font are more likely to have shorter durations and can choose the more farsighted intertemporal choice (i.e., LL) than those who use the red font. Students using blue fonts are more likely to perceive the difference between the two options chosen across time (∆payoff A, B) to be greater than the difference between the two options in the payoff dimension (∆time A, B), leading to farsighted choices compared with those using red fonts. Serial mediation was also found. Conclusion The findings revealed why font color influences intertemporal choice. This study revealed the mediating role that time perception and intradimensional difference comparison play in the association between font color and intertemporal choice.